Studies on glyceraldehyde 3 phosphate dehydrogenase - Clark-Walker, G (1965)
The enzyme glyceraldehyde-3-phosphate dehydrogenase E.G.1.2.1.12 has been prepared from rabbit muscle by ammonium sulphate fractionation. After four refractionations the levels of the contaminating enzymes α GDH & TP1 were found to be 25 parts and 1 part per million and contamination by myokinase was 3 parts per thousand. The activity of the purified enzyme was found to be in the region of 14,000 - 17,000 moles NADH/min/105g protein. During refractionation of the purified enzyme in the presence of excess NAD+ the enzyme was found to crystallize in rectangular plates instead of the familiar rhomboidal plates. This observation was investigated in terms of the nucleotide content of the protein and the presence of a nucleotide differing from both NAD+ and NADH was detected. Different preparations of the enzyme from rabbit muscle were found to contain amounts of the unidentified nucleo- tide varying from 0·60 - 1·63 moles/105g of protein. In conjunction with NAD+ the total nucleotide bound to the protein always amounted to 2·45 moles/105g protein. The nucleotide has been isolated by passage of the protein down a DEAE sephadex column at pH 9·5 - 10·0 and has subsequently been shown to contain adenine ribose and phosphate in the ratio of 1 : 2 : 2. The nucleotide was also shown to have the same electrophoretic mobility as NADH but no 340 mμ absorption and to have a molar absorptivity of 26·0 × 103 at the absorption maximum of 266 mμ. The nucleotide was compared with NADH-X prepared by the G3PD catalysed transformation of NADH and the nucleotide arising from the phosphate catalysed transformation of NADH. Although the initial products of both these transformations appear to be identical with the nucleotide isolated from the enzyme the compounds obtained, with absorption maxima at 264 mμ and molar absorptivities between 21·0 - 22·2 × 103, are thought to have undergone further modification during the isolation procedures. The nucleotide isolated from the protein has not been unequivocally characterized but by analogy with the spectra of other transformed nicotinamides it is thought to be the 6 - OH adduct formed by hydration of the 5:6 double bond of NADH. The finding that the protein isolated from rabbit muscle contains an additional nucleotide other than NAD+ resolves the discrepancy in the literature relating to the number of binding sites on the protein and the apparent liberation of a further binding site on charcoal treatment of the protein. The increased absorption and unexpected shoulders in the absorption spectrum of the holo enzyme containing bound NAD+ have been investigated by a difference spectrum technique and found to be due to the shielding of a tryptophan residue of the protein from interaction with the solvent. The shielding or burying of tryptophan has also been observed when NADH and ADFR are bound to the protein and in the former case the protein is thought to undergo a configurational change leading to the exposure of a previously 'buried' tyrosine residue. The extent of binding of NAD+ to the enzyme has been followed by observing the increase in the 360 mμ absorption bond resulting from the interaction between nucleotide and protein. The formation of the charge transfer complex was found to be markedly different from the expected titration curve based on the small dissociation constant for protein and NAD+. Protein concentration was shown to influence the titration curves and this has suggested that subunit effects may be responsible. The extent of reduction of enzyme bound NAD+ by added G3P has been investigated and shown to be associated with the binding of G3P to the protein : NAD+ complex. Moreover the reduction of protein bound NAD+ was also found to be influenced by the protein concentration, proportionally less NADH being produced on increasing the protein concentration. No evidence was found that the hydration product of NADH, was concerned in the non-stoichiometry of reduction of bound NAD+. Also. the observation was made that NADH produced in situ by reduction of protein bound NAD+ was not transformed into NADH - X in the slow NADH transformation reaction catalysed by the enzyme. These facts have led to the conclusion that the NADH - X found on the protein after isolation from rabbit muscle is an artifact of the isolation procedure and is formed as a result of the breakdown of acyl enzyme which leads to the catalysed transformation of the bound NADH to NADH - X. The titration of the protein with G3P in the presence of phosphate, sulphate or arsenate was found to yield identical curves for the reduction of NAD+. It therefore appears that the overall equilibrium of the enzyme catalysed reaction is not established and that a further step must be included in the currently accepted reaction mechanism of the enzyme. The number of sulphydryl groups on the protein has been determined using an amperometric technique with phenyl mercuric hydroxide. The value of 10·2 - 10·4 SH residues/105g of protein, gives a value of 12 - SH residues/117,000g of protein. A value for the molecular weight in the region of 120,000 is supported by the finding that the holo enzyme binds 3 NAD+ molecules/122,000g of protein. The disappearance in protein sulphydryl groups on acyl enzyme formation was studied with acetyl phosphate, acetaldehyde, and G3P as subtrates of the enzyme. Only 0·55 and 0·75 SH groups/105g. of protein were found to disappear in the presence of the first two substrates and no difference in sulphydryl titre could be found between protein in the presence or absence of G3P. The results with acetylphosphate support earlier workers who found that acetyl phosphate caused a disappearance in titratable -SH groups of the protein and in addition the data with acetaldelyde confirm the view that the thiol ester so formed is a true catalytic intermediate. The fact that no thiol ester formation can be detected with the natural substrate, which is oxidized 30,000 times faster than acetaldelyde, was not surprising as a true catalytic intermediate must be expected to be broken down as rapidly as it is formed.